Bench scale catalytic fast pyrolysis of empty fruit bunches over low cost catalysts and HZSM-5 using a fixed bed reactor - Ro, Donghoon; Kim, Young-Min; Lee, In-Gu; Jae, Jungho; Jung, Sang-Chul; Kim, Sang Chai; Park, Young-Kwon (ELSEVIER SCI LTD, 2018)
The performance of HZSM-5 and low cost catalysts, such as the spent fluid catalytic cracking (FCC) catalyst, bentonite, dolomite, and olivine, on the production of high-quality bio-oil during the catalytic pyrolysis of empty fruit bunches (EFBs) was compared in a bench scale fixed bed reactor. The spent FCC and HZSM-5 catalysts showed higher cracking performance than bentonite, dolomite, and olivine. The catalytic pyrolysis of EFB over the spent FCC catalyst showed higher selectivity to phenol (31.5%) and alkyl phenols (26.0%) due to the effective dealkoxylation of guaiacols and syringols, whereas HZSM-5 provided the higher selectivity to aromatic hydrocarbons (40.4%). The catalytic pyrolysis of EFB over the spent FCC catalyst and HZSM-5 produced bio-oil with a higher heating value (28.44-31.18 MJ/kg) than other bio-oils obtained over bentonite (27.89 MJ/k,g) and olivine (16.83 MJ/kg). The bio-oils obtained from the catalytic pyrolysis of EFB over the spent FCC and HZSM-5 catalysts also had a lower viscosity (7.0-13.5 mm(2)/s) than those (13.8-22.1 mm(2)/s) over the other catalysts, even after accelerated aging at 80 degrees C for 1 day. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: BIO-OIL; BIOMASS PYROLYSIS; PALM; AROMATICS; CRACKING; DECOMPOSITION; CONVERSION; CELLULOSE; PRODUCT; OLEFINS